SOCIO-PSYCHOLOGICAL FEATURES OF THE PREVENTION OF CONFLICT SITUATIONS BETWEEN TEACHER AND STUDENT (Conferencea, 2023)
This article is to reveal the content of psychological preparation of students at the stage of university education for the management of interpersonal conflicts in the educational process of the school. The authors present the results of an empirical study of the future teacher's willingness to regulate interpersonal conflicts. The content and features of the implementation of the elective course "Psychology of conflict" are disclosed, during the study of which it is possible to purposefully form the competencies of a future teacher in matters of conflict prevention and resolution both in their own lives and in professional activities. The article is intended for students, postgraduates, teachers of pedagogical universities and teachers of educational organizations.